Tetrandrine suppresses the growth of human osteosarcoma cells by regulating multiple signaling pathways. Issue 1 (1st January 2021) - Wang, Nan; Yang, Shengdong; Tan, Tao; Huang, Yanran; Chen, Yangmei; Dong, Chaoqun; Chen, Jin; Luo, Xiaoji
ABSTRACT: Although osteosarcoma (OS) is the most common malignant tumor among juvenile bone tumors, its treatment plan and clinical outcome have not improved significantly in recent decades. Tetrandrine (TET), a Chinese medicine that is usually used in the therapy of silicosis, hypertension and arthritis, has been confirmed by many studies to possess potent antitumour growth properties, but there are different limitations when describing specific mechanisms. Here, we found that TET can obviously prevent the proliferation, migration and invasion of both 143B and MG63 cells and promote their apoptosis in vitro. Our results for luciferase reporter and Western blotting assays show that TET may exert its antitumour activity by regulating multiplex signaling pathways, including the MAPK/Erk, PTEN/Akt, Juk and Wnt signaling pathways. Furthermore, the regulatory effect of TET on OS cells and related signaling pathways was verified again in vivo. Our findings suggest that the anticancer function of TET on human OS may be mediated by its targeting of multiple signaling pathways and that TET may be used as a single drug or in combination with other drugs during the treatment of OS.